STRATEGI BADAN PERENCANAAN PEMBANGUNAN RISET DAN INOVASI DAERAH KABUPATEN SUMBAWA DALAM MENANGANI ISU STRATEGIS INFRASTRUKTUR - Feny Dwi Maharani; Dedi Supriadi (Jurnal Ekonomi & Bisnis, 2026)
This research aims to analyze the strategy of the Regional Development Planning, Research and Innovation Agency (Bappeda) of Sumbawa Regency in addressing strategic infrastructure issues for 2024-2025. Infrastructure is one of the main strategic issues in the Sumbawa Regency RPJMD 2021-2026, playing an important role in supporting economic growth, equitable development, and achieving the Sustainable Development Goals (SDGs). This research employs a qualitative approach with a descriptive method, using data collection techniques through observation, interviews, and documentation. Data analysis uses strategic management theory covering strategy formulation, strategy implementation, and strategy evaluation, as well as public policy implementation theory. The results show that Bappeda Sumbawa Regency has integrated infrastructure development into regional planning documents through cross-Regional Apparatus Organization (OPD) coordination and alignment with national policies and SDGs. However, implementation still faces constraints in the form of budget limitations, human resources, and suboptimal inter-agency coordination. Institutional capacity strengthening and cross-sector synergy are needed so that infrastructure development strategies can run effectively and sustainably.